Hopkins Papers - Grady County Historical Society (My University, 1939)
This item contains a newspaper and a letter discussing the legislation that created Grady County. The newspaper is dated in 2005, and the letter is dated in 1939.
1 PDF file with 2 pages and a title page
Keywords: Grady County (Ga.)